Sex-specific differences in zebrafish brains - BEREKETOĞLU, CEYHUN (My University, 2022)
In this systematic review, we highlight the diferences between the male and female zebrafsh brains to understand their diferentiation and their use in studying sex-specifc neurological diseases. Male and female brains display subtle diferences at the cellular level which may be important in driving sex-specifc signaling. Sex diferences in the brain have been observed in humans as well as in non-human species. However, the molecular mechanisms of brain sex diferentiation remain unclear. The classical model of brain sex diferentiation suggests that the steroid hormones derived from the gonads are the primary determinants in establishing male and female neural networks. Recent studies indicate that the developing brain shows sex-specifc diferences in gene expression prior to gonadal hormone action. Hence, genetic diferences may also be responsible for diferentiating the brain into male and female types. Understanding the signaling mechanisms involved in brain sex diferentiation could help further elucidate the sex-specifc incidences of certain neurological diseases. The zebrafsh model could be appropriate for enhancing our understanding of brain sex diferentiation and the signaling involved in neurological diseases. Zebrafsh brains show sex-specifc diferences at the hormonal level, and recent advances in RNA sequencing have highlighted critical sexspecifc diferences at the transcript level. The diferences are also evident at the cellular and metabolite levels, which could be important in organizing sex-specifc neuronal signaling. Furthermore, in addition to having one ortholog for 70% of the human gene, zebrafsh also shares brain structural similarities with other higher eukaryotes, including mammals. Hence, deciphering brain sex diferentiation in zebrafsh will help further enhance the diagnostic and pharmacological intervention of neurological diseases. Keywords: Steroid hormones, Gonads, Diferentiation, Disease, Neurons
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Tıbbi Genetik; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Temel Bilimler; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; Medical Genetics; Life Sciences; Molecular Biology and Genetics; Natural Sciences; ENDOKRİNOLOJİ VE METABOLİZMA; Klinik Tıp; Klinik Tıp (MED); GENETİK VE KALITIM; Moleküler Biyoloji ve Genetik; Yaşam Bilimleri (LIFE); ENDOCRINOLOGY & METABOLISM; CLINICAL MEDICINE; Clinical Medicine (MED); GENETICS & HEREDITY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); Genetik; Endokrinoloji; Moleküler Biyoloji; Endokrin ve Otonom Sistemler; Genetik (klinik); Endokrinoloji, Diyabet ve Metabolizma; Genetics; Endocrinology; Molecular Biology; Endocrine and Autonomic Systems; Genetics (clinical); Endocrinology, Diabetes and Metabolism; Steroid hormones; Gonads; Differentiation; Disease; Neurons; RADIAL GLIAL-CELLS; DIMORPHIC GENE-EXPRESSION; IN-SITU HYBRIDIZATION; ADULT ZEBRAFISH; DANIO-RERIO; TARGETED DISRUPTION; THYROID-HORMONE; CHROMOSOME EVOLUTION; DETERMINING REGION; ANDROGEN RECEPTOR; Steroid hormones; Gonads; Diferentiation; Disease; Neurons